Intervention fidelity in the definitive cluster randomised controlled trial of the Healthy Lifestyles Programme (HeLP) trial: findings from the process evaluation - Lloyd, Jenny (Int J Behav Nutr Phys Act, 2017)
BACKGROUND: The Healthy Lifestyles Programme (HeLP) was a novel school-located intervention for 9–10 year olds, designed to prevent obesity by changing patterns of child behaviour through the creation of supportive school and home environments using dynamic and creative delivery methods. This paper reports on both the quantitative and qualitative data regarding the implementation of the HeLP intervention in the definitive cluster randomised controlled trial, which was part of the wider process evaluation. METHODS: Mixed methods were used to collect data on intervention uptake, fidelity of delivery in terms of content and quality of delivery of the intervention, as well as school and child engagement with the programme. Data were collected using registers of attendance, observations and checklists, field notes, focus groups with children and semi-structured interviews with teachers. Qualitative data were analysed thematically and quantitative data were summarized using descriptive statistics. RESULTS: All 16 intervention schools received a complete or near complete programme (94–100%), which was delivered in the spirit in which it had been designed. Of the 676 children in the intervention schools, over 90% of children participated in each phase of HeLP; 92% of children across the socio-economic spectrum were deemed to be engaged with HeLP and qualitative data revealed a high level of enjoyment by all children, particularly to the interactive drama workshops. Further evidence of child engagment with the programme was demonstrated by children’s clear understanding of programme messages around marketing, moderation and food labelling. Thirteen of the intervention schools were deemed to be fully engaged with HeLP and qualitative data revealed a high level of teacher ‘buy in’, due to the programme’s compatability with the National Curriculum, level of teacher support and use of innovative and creative delivery methods by external drama practitioners. CONCLUSION: Our trial shows that it is possible to successfully scale up complex school-based interventions, engage schools and children across the socio-economic spectrum and deliver an intervention as designed. As programme integrity was maintained throughout the HeLP trial, across all intervention schools, we can be confident that the trial findings are a true reflection of the effectiveness of the intervention, enabling policy recommendations to be made. TRIAL REGISTRATION: ISRCTN15811706. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12966-017-0616-6) contains supplementary material, which is available to authorized users.